Philosophy of Landscape in Fedor Stepun’s Model of Socio-Cultural Development - Zagirnyak, Mikhail Yu (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2023)
The manifestation of the significance of geographic specificity in the formation and development of society is the most crucial research vector in the study of socio-philosophical doctrines. The tradition of conceptualizing the meaning of geography in the history of Russia was significantly contributed by Sergey Solovyov and Vasily Klyuchevsky. Fyodor Stepun also correlated geographic conditions and social practices within the philosophy of landscape, which he successfully integrated into his socio-philosophical doctrine. This research paper is undertaken to reveal the essential principles of Stepun's social philosophy and to determine the features of his argumentation, which he used to interpret the mechanism of the socio-cultural process. Comparing the landscapes of Europe and Russia is Stepun's favorite method to focus on entirely different systems of social practices formed in different natural conditions. The limited/unlimited opposition is the foundation of Stepun's landscape philosophy. Stepun emphasizes that religion plays a significant role in forming the existence of social beings. Religion creates and maintains the unity of society, without which it is impossible to include geographic space in social practices. Religion forms a collective social subject from a multitude of individuals and collective formations and from their various activities - a unity tradition: a culture that has its strategy for the social development of the landscape. Stepun believed that the loss of religion's functionality as an instrument of social cohesion leads, in the long term, to the death of culture. Orthodox politics will help in the conditions of Russia's infinite space to ensure social cohesion and thus incorporate the landscape into social area. This policy knows the unique role of religion in socio-cultural development. Thanks to the Orthodox policy, it is possible to integrate the Russian landscape into the economic system effectively.